Giving the Past a Future: Community Archaeology, Youth Engagement and Heritage in Quinhagak, Alaska - Hillerdal, Charlotta; Watterson, Alice; Williams, M. Akiqaralria; Alaskuk Strunk, Lonny; Nalikutaar Cleveland, Jacqueline; Joseph, Corey (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2022)
Initiated by the descendant community of Quinhagak and endorsed by village Elders, the Nunalleq Archaeology Project was unique for Yup’ik Alaska when it began in 2009. Since then, this embedded community project has provided the village with over a decade of archaeological presence in the form of excavations, finds processing, conservation lab work, and, since 2018, a local repository housing the entire archaeological collection.Accounts of collaborations between archaeologists and Indigenous communities often focus on Elders and cultural bearers. However, whilst these collaborators are, and continue to be, invaluable for the Nunalleq project, here we want to acknowledge the generation of young adults who have grown up with the Project, and to whom archaeological finds and artifacts are now an intrinsic part of their heritage. This paper discusses how the Nunalleq Archaeology Project has come to influence local heritage, and how community engagement has in turn shaped the archaeological practice and co-designed outreach work. We constructively reflect upon insights borne from a decade of collaborative practice and critically ask how such community collaborations may be strengthened for the future.